2018
DOI: 10.1016/s2095-3119(17)61749-0
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis of salt-responsive genes and SSR marker exploration in Carex rigescens using RNA-seq

Abstract: Carex rigescens (Franch.) V. Krecz is a wild turfgrass perennial species in the Carex genus that is widely distributed in salinised areas of northern China. To investigate genome-wide salt-response gene networks in C. rigescens, transcriptome analysis using high-throughput RNA sequencing on C. rigescens exposed to a 0.4% salt treatment (Cr_Salt) was compared to a non-salt control (Cr_Ctrl). In total, 57 742 546 and 47 063 488 clean reads were obtained from the Cr_Ctrl and Cr_Salt treatments, respectively. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Technically, molecular marker is an important method for population genetics research [50,51]. In this study, 4138 SSR genes and 114,977 SNP loci were identified from the transcriptome of D. houi, mono-nucleotide repeat is the main type of SSR, accounting for the largest proportion, the trinonucleotide repeat was the most common type, which is similar to results of some previous research on Epacromius coerulipes [52], Bactrocera dorsalis [53].…”
Section: Discussionsupporting
confidence: 81%
“…Technically, molecular marker is an important method for population genetics research [50,51]. In this study, 4138 SSR genes and 114,977 SNP loci were identified from the transcriptome of D. houi, mono-nucleotide repeat is the main type of SSR, accounting for the largest proportion, the trinonucleotide repeat was the most common type, which is similar to results of some previous research on Epacromius coerulipes [52], Bactrocera dorsalis [53].…”
Section: Discussionsupporting
confidence: 81%
“…Carex , one of the largest genus in Cyperaceae, contains more than 2000 species and plays important roles in turfgrass and forage production as well as in ecological conservation [1]. However, our current knowledge on Carex species transcriptomes is mainly based on gene expression analysis of Carex rigescens using NGS technologies [3]. Moreover, the Carex.…”
Section: Discussionmentioning
confidence: 99%
“…The wide application of transcriptome sequencing has promoted plant breeding and revealed gene regulation networks in plants [2]. However, few studies have focused on the transcriptome of Carex L., with previous studies being limited to physiological investigation and stress-resistance evaluation [3, 4]. Consequently, progress in the study of the transcriptome of the genus lags far behind.…”
Section: Introductionmentioning
confidence: 99%
“…Since no sequences for C. muskingumensis were available, Carex rigescens sequences deposited in GeneBank or SRA database (Sequence Read Archive accession No. SRX2755644) [ 27 ] were used for primer designing. Arabidopsis thaliana and Zea mays nucleotide sequences were used as query sequences for performed BLASTN search.…”
Section: Methodsmentioning
confidence: 99%
“…The information on sedges’ molecular responses to osmotic stress and their adaptation mechanisms is limited [ 27 , 28 , 29 ]. To address this issue, our study aims at identifying best RGs for C. muskingumensis under salt and drought stress.…”
Section: Introductionmentioning
confidence: 99%